UPAYA PENANGKAPAN PELAKU TINDAK PIDANA KORUPSI YANG KABUR KE LUAR NEGERI - Muhammad Daffa Izzulhaq (JURNAL LEGISIA, 2023)
This research was conducted with the aim of unraveling the efforts that can be made in arresting corruption criminals who fled abroad. Using normative juridical research methods, the author will present a legal study based on positive law in force in Indonesia, which will then be further elaborated in this study. Corruption Crime is a special criminal act which has different arrangements compared to general criminal acts, it is contained in UU No. 31 of 1999 concerning the Eradication of Corruption Crimes as amended by UU No. 20 of 2001 concerning Amendments to UU No. 31 of 1999 concerning the Eradication of Corruption Crimes. In efforts to arrest perpetrators of corruption crimes who flee abroad, it can be done with applicable procedures, namely; extradition treaty contained in Law No. 1 of 1979 on Extradition, and also through the Mutual Legal Assistance agreement contained in Law No. 1 of 2006 on Mutual Legal Assistance in Criminal Matters, UU No. 15 of 2008 on Ratification of the Treaty on Mutual Legal Assistance in Criminal Matters, dan ASEAN Mutual Legal Assistance in Criminal Matters 2004. In the context of corruption crimes, this Extradition Treaty is used as an effort and procedure for arresting perpetrators of corruption crimes who commit corruption crimes outside the territory of the state jurisdiction, And it is also used as an effort to arrest perpetrators of corruption who flee outside the jurisdiction of a country, so that this extradition treaty is an alternative that can be taken by law enforcement officials to arrest perpetrators of corruption crimes. In the context of corruption, Mutual Legal Assistance is an arrangement for cooperation between countries (bilateral and multilateral) in preventing and eradicating transnational crimes, especially corruption crimes.